2019
DOI: 10.1158/2159-8290.cd-19-0367
|View full text |Cite
|
Sign up to set email alerts
|

Acquired On-Target Clinical Resistance Validates FGFR4 as a Driver of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer mortality worldwide with no clinically confi rmed oncogenic driver. Although preclinical studies implicate the FGF19 receptor FGFR4 in hepatocarcinogenesis, the dependence of human cancer on FGFR4 has not been demonstrated. Fisogatinib (BLU-554) is a potent and selective inhibitor of FGFR4 and demonstrates clinical benefi t and tumor regression in patients with HCC with aberrant FGF19 expression. Mutations were identifi ed in the gatekeeper and hinge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 25 publications
2
71
0
Order By: Relevance
“…This phase I study with the highly potent and selective FGFR4 inhibitor fi sogatinib clinically validates the therapeutic potential of targeting the FGF19-FGFR4 pathway by demonstrating for the fi rst time that FGFR4 inhibition is tolerable and efficacious in advanced HCC expressing FGF19. The fi ndings of this study, together with the identifi cation of on-target fi sogatinib-resistance mutations in FGFR4 ( 22 ), confi rm the driver status of the FGF19-FGFR4 pathway in HCC with FGF19 overexpression.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This phase I study with the highly potent and selective FGFR4 inhibitor fi sogatinib clinically validates the therapeutic potential of targeting the FGF19-FGFR4 pathway by demonstrating for the fi rst time that FGFR4 inhibition is tolerable and efficacious in advanced HCC expressing FGF19. The fi ndings of this study, together with the identifi cation of on-target fi sogatinib-resistance mutations in FGFR4 ( 22 ), confi rm the driver status of the FGF19-FGFR4 pathway in HCC with FGF19 overexpression.…”
Section: Discussionmentioning
confidence: 51%
“…1B). Fisogatinib also has a high affinity for FGFR4 that is approximately 100-fold higher than its affinity for FGFR1 and almost 1,000-fold higher than its affinity for FGFR2 and FGFR3 (22). Fisogatinib dose-dependently blocked the downstream signaling of FGFR4 in Hep3B cells that were further activated with exogenous FGF19 and in MDA-MB-453 cells with mutated and constitutively active FGFR4 (Supplementary Fig.…”
Section: Fisogatinib Selectively Inhibits Fgfr4mentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that there are a number of amino-acid substitutions in the tyrosine kinase domains of FGFR4 (Dutra et al, 2015;Katoh, 2016). FGF401 (Weiss et al, 2019;Zhou et al, 2019), BLU9931 , and BLU-554 (Hatlen et al, 2019;Kim et al, 2019) have been reported to be the most highly potent and selective FGFR4 inhibitors. Representative FGFR4 inhibitors that are currently undergoing clinical trials were shown in Table 1.…”
Section: Targeting the Fgf19-fgfr4 Pathway Fgfr4 Inhibitorsmentioning
confidence: 99%
“…It is well known that molecularly targeted therapy tends to induce specific and acquired resistance rather quickly in vitro and in vivo. Several recent clinical studies showed resistance mechanisms against FGFR inhibitors, i.e., FGFR gene point mutations and pathway activation such as MET [16,[38][39][40]. For example, EGFR suppresses FGFR3 expression in cells that are resistant to FGFR3 inhibitors and dominates the signal input to downstream pathways [41].…”
Section: Discussionmentioning
confidence: 99%